PERTUMBUHAN DAN KOMPOSISI RANTAI PANJANG POLYISOPRENOID PADA MANGROVE Avicennia marina (Forsk). DI BAWAH CEKAMAN SALINITAS - Hamsyah Rianda Harahap; Mohammad Basyuni; Lollie AP Putri (Program studi Kehutanan USU, 2015)
Mangrove plants have ability to remove excess of salt and contain secondary metabolite to adapt to wide salinity. The purpose of this study was to determine the best salinity level for growth of A. marina seedlings and to evaluate the effect on long-chain polyisoprenoid composition. A. marina seed was used with 5 treatments,-i.e 0%, 0.5%, 1.5%, 2%, and 3% grown for 3 months. Results showed that the optimum growth characterized by height, number of leaves, wet weight of root, wet weight of shoot, dry weight of root, dry weight of shoot, and ratio of shoot to root of A. marina seedlings in 2% concentration. The optimum of diameter was in 0% salinity. Polyisoprenoid showed that A. marina seedlings in 3% salinity was higher content than control. Key Words : Mangrove, Avicennia marina, Salt Salinity, Polyisoprenoid, Secondary Metabolite.